Система психокоррекции и социальной реабилитации мужчин с алкогольной зависимостью = System of psychocorrection and social rehabilitation for men suffering from alcohol dependence - D. V. Vozny (Journal of Education, Health and Sport, 2015)
Vozny D. V. Система психокоррекции и социальной реабилитации мужчин с алкогольной зависимостью = System of psychocorrection and social rehabilitation for men suffering from alcohol dependence. Journal of Education, Health and Sport. 2015;5(4):102-108. ISSN 2391-8306. DOI: 10.5281/zenodo.16640